Interfaith Marriage in Islamic Law: A Meta-Analysis and Systematic Review - Mas Agus Priyambodo (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2025)
This meta-analysis and systematic review explore the issue of interfaith marriage within Islamic law, analyzing both traditional and contemporary perspectives. While classical Islamic jurisprudence generally prohibits Muslim women from marrying non-Muslim men, modern scholarship increasingly challenges these restrictive interpretations, advocating for a more inclusive approach based on the ethical principles of Sharia. The review examines the role of gender in shaping these legal norms, highlighting the disproportionate impact on Muslim women, and explores regional variations in the application of Islamic marriage laws. It further discusses the influence of legal pluralism and fatwas in shaping public policy and social acceptance of interfaith unions. The study also identifies significant gaps in empirical research regarding the lived experiences of interfaith couples, suggesting that future studies should focus on understanding how these couples navigate legal, social, and religious challenges. The findings recommend that both legal reform and scholarly reinterpretation are essential to accommodate the realities of interfaith marriages while respecting Islamic values and promoting human rights. By offering a more flexible and justice-oriented approach, Islamic law can better address the needs of interfaith families in contemporary multicultural societies.